2005
DOI: 10.1001/archderm.141.4.510
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Lentigo Maligna (Melanoma In Situ) With the Immune Response Modifier Imiquimod

Abstract: Background: Surgical excision is the treatment of choice for lentigo maligna (LM), or melanoma in situ. Topical application of imiquimod, a local immune response modifier, is a novel therapeutic approach that leads to LM tumor clearance. This pilot, open-label, nonrandomized study evaluates the efficacy of imiquimod in patients with LM and other systemic problems that make them poor surgical risks.Observations: Six biopsy-proven cases of LM from 5 patients (age range, 67-80 years) in whom standard surgical the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 21 publications
1
79
0
Order By: Relevance
“…In addition, several controlled clinical trials as well as many smaller series of cases and case reports have demonstrated that imiquimod is also effective against a variety of primary skin cancers as well as cutaneous metastases of some malignancies. Cutaneous tumors that have responded well to topical treatment with imiquimod include basal cell carcinomas (Sterry et al, 2002;BathHextall et al, 2004;Geisse et al, 2004;Gollnick et al, 2005;Schulze et al, 2005), keratoacanthomas (Dendorfer et al, 2003;Peris et al, 2003), actinic keratoses (Stockfleth et al, 2001(Stockfleth et al, , 2002Lebwohl et al, 2004;Szeimies et al, 2004;Korman et al, 2005) and Bowen's disease (the latter two entities represent epidermal carcinoma in situ) (Patel et al, 2006;Peris et al, 2006), cutaneous metastases of melanoma (Steinmann et al, 2000;Bong et al, 2002;Ugurel et al, 2002;Wolf et al, 2003;Zeitouni et al, 2005), some cases of primary melanoma in situ (Fleming et al, 2004;Kamin et al, 2005;Ray et al, 2005;Wolf et al, 2005;Lonsdale-Eccles et al, 2006) and cutaneous T-cell lymphomas (Suchin et al, 2002;Dummer et al, 2003b;Chong et al, 2004;Deeths et al, 2005). Clinical responses of cutaneous neoplasias to topical treatment with imiquimod have also been observed in difficult-to-treat patient populations, such as organ transplant patients under immunosuppressive therapy (Smith et al, 2001;Prinz et al, 2004;Brown et al, 2005) or Xeroderma pigmentosum patients suffering from rapid development of multiple UV-induced cutaneous malignancies …”
Section: Antitumoral Efficacy Of Tlr7/8 Agonists In Clinical Trialsmentioning
confidence: 99%
“…In addition, several controlled clinical trials as well as many smaller series of cases and case reports have demonstrated that imiquimod is also effective against a variety of primary skin cancers as well as cutaneous metastases of some malignancies. Cutaneous tumors that have responded well to topical treatment with imiquimod include basal cell carcinomas (Sterry et al, 2002;BathHextall et al, 2004;Geisse et al, 2004;Gollnick et al, 2005;Schulze et al, 2005), keratoacanthomas (Dendorfer et al, 2003;Peris et al, 2003), actinic keratoses (Stockfleth et al, 2001(Stockfleth et al, , 2002Lebwohl et al, 2004;Szeimies et al, 2004;Korman et al, 2005) and Bowen's disease (the latter two entities represent epidermal carcinoma in situ) (Patel et al, 2006;Peris et al, 2006), cutaneous metastases of melanoma (Steinmann et al, 2000;Bong et al, 2002;Ugurel et al, 2002;Wolf et al, 2003;Zeitouni et al, 2005), some cases of primary melanoma in situ (Fleming et al, 2004;Kamin et al, 2005;Ray et al, 2005;Wolf et al, 2005;Lonsdale-Eccles et al, 2006) and cutaneous T-cell lymphomas (Suchin et al, 2002;Dummer et al, 2003b;Chong et al, 2004;Deeths et al, 2005). Clinical responses of cutaneous neoplasias to topical treatment with imiquimod have also been observed in difficult-to-treat patient populations, such as organ transplant patients under immunosuppressive therapy (Smith et al, 2001;Prinz et al, 2004;Brown et al, 2005) or Xeroderma pigmentosum patients suffering from rapid development of multiple UV-induced cutaneous malignancies …”
Section: Antitumoral Efficacy Of Tlr7/8 Agonists In Clinical Trialsmentioning
confidence: 99%
“…Tryptophan metabolites from malassezia yeast induce apoptosis in human melanocytes, which leads to depigmentation of the skin (pityriasis versicolor) [104]. Imiquimod, an immune response modifier that stimulates cytotoxic T-cell-mediated responses through activation of toll-like receptors, leads to tumor destruction and depigmentation in lentigo-maligna lesions [105,106].…”
Section: Biological Effectorsmentioning
confidence: 99%
“…In contrast, despite the above considerations, CMIS is linked to some health concerns and unsolved debates regarding its clinicopathologic diagnosis [19 -24], therapeutic/follow-up management [20,[25][26][27][28][29], and prognostic relevance [24, 30 -32].…”
Section: Introductionmentioning
confidence: 99%